Plato and the Individual - Hall, Robert William. author. aut Link
VIII, 224 p. 1 illus.
Keywords: In this study of Plato's theory of the individual, I propose to show that Plato is deeply concerned with the achievement by each person of the moral excellence appropriate to man. Plato exhibits profound interest in the moral well being of each individual, not merely those who are philosophically gifted. Obviously my study is in opposition with a traditional line of interpretation which holds that Plato evinces small concern for the ordinary individual, the "common man" of today. According to this interpretation Plato's chief interest, shown especially in the Republic, is with the philosophically endowed, whose knowledge penetrates to and embraces the realm of forms; this is a world which must remain for the common man an unfathomable mystery in its totality. Although he is unable to grasp the knowledge of the forms necessary for genuine morality, the ordinary individual may, if he is fortunate enough to live in a polis ruled by philosophers, gain a sort of secondary or "demotic" morality. Through the me chanical development of the right kind of habits, through faithful obedience to the decrees of the rulers and the laws of the polis, the many who are incapable of comprehending the true bases of morality will attain a second best, unreflective morality accompanied by happi ness.